Methodologies and technologies for networked enterprises artdeco: adaptive infrastructures for decentralised organisations - Anastasi, Giuseppe (Lecture Notes in Computer Science, 2012)
The need for flexibility and globalization forces enterprises to decentralize their activities and continuously (re)structure their networks of relationships regarding both their productive "supply chains" and their design and innovation processes. The goal of the ArtDeco project, funded by the Italian Ministry of Education and Scientific Research under the FIRB program (funding for basic research), has been to address these issues by proposing solutions from three main perspectives: the organizational perspective aimed at studying how companies work in a network and how their design processes can benefit from collaboration with other companies; the informational perspective focusing on how to acquire relevant knowledge from unstructured information and processes and on how to organize and manage such knowledge; and the infrastructural perspective focusing on understanding how self-adaptive workflows and software systems can help in supporting the dynamic interconnection of enterprises. The book contains a collection of papers offering an overview of the main results produced by the ArtDeco project. It has been structured into the following four main parts: organizational issues: methodologies, empirical contexts and policies; software methodologies and technologies; knowledge elicitation and management; and management of peripheral devices. It also includes a case study used throughout the book as a reference example.